2016
DOI: 10.1016/j.bbrc.2016.09.049
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling of esophageal adenocarcinoma using Methylation Ligation-dependent Macroarray (MLM)

Abstract: Most types of cancer cells are characterized by aberrant methylation of promoter genes. In this study, we described a rapid, reproducible, and relatively inexpensive approach allowing the detection of multiple human methylated promoter genes from many tissue samples, without the need of bisulfite conversion. The Methylation Ligation-dependent Macroarray (MLM), an array-based analysis, was designed in order to measure methylation levels of 58 genes previously described as putative biomarkers of cancer. The perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Once the selected material has been removed from the sections, a relevant method for analysis of methylation levels needs to be selected. Some methods utilized for the detection of DNA methylation levels [42][43][44][45] : Digestion-based assay (PCR, qPCR, RT-PCR, cold PCR); High resolution melting luminometric methylation assay; HPLC-UV; Mass spectrometry; ELISA-based methods; Amplified fragment length polymorphism; Restriction fragment length polymorphism; Luminometric methylation assay; Pyrosequencing; Bisulfite sequencing; ELISA; Methylation ligation-dependent macro-array; High-throughput measurement technologies.…”
Section: Methods For Determining Dna Methylationmentioning
confidence: 99%
“…Once the selected material has been removed from the sections, a relevant method for analysis of methylation levels needs to be selected. Some methods utilized for the detection of DNA methylation levels [42][43][44][45] : Digestion-based assay (PCR, qPCR, RT-PCR, cold PCR); High resolution melting luminometric methylation assay; HPLC-UV; Mass spectrometry; ELISA-based methods; Amplified fragment length polymorphism; Restriction fragment length polymorphism; Luminometric methylation assay; Pyrosequencing; Bisulfite sequencing; ELISA; Methylation ligation-dependent macro-array; High-throughput measurement technologies.…”
Section: Methods For Determining Dna Methylationmentioning
confidence: 99%
“…COL14A1 aberrant methylation has been reported in ESCC (16), as well as in renal cell carcinoma, sarcomas, and endometrial carcinoma (28,31,32), whereas hypomethylation has been shown in coronary artery disease (33). GPX3 promoter methylation has been shown in ESCC and esophageal glandular lesions, including Barrett's esophagus and EA (30,34,35). In the same vein, ZNF569 promoter hypermethylation has been associated with glandular lesions, like Barrett's esophagus (17) in comparison with the normal esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…COL14A1 aberrant hypermethylation has been reported in ESCC (16), as well as renal cell carcinoma, sarcomas and endometrial carcinoma (35)(36)(37), whereas hypomethylation has been shown in coronary artery disease (38). GPX3 promoter hypermethylation has been reported in ESCC and esophageal glandular lesions, including Barrett's esophagus and EA (17,18,39). In the same vein, ZNF569 promoter hypermethylation has been associated with glandular lesions, like Barrett's esophagus (19) in comparison with normal esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, GPX3 promoter methylation levels did not differ between EA from normal tissues, although a few cases disclosed higher methylation levels (data not shown). Notwithstanding, different sample processing (fresh frozen tissues vs. FFPE) (17,39), different methodologies to assess GPX3 methylation levels among studies (qMSP vs. MSP vs. methylation ligation-dependent macroarray vs. pyrosequencing) and the smaller size of some cohorts (17,18) may explain some disparate results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation